The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pi.5160
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene polymerization using vanadium catalyst supported on silica modified by pyridinium ionic liquid

Abstract: Vanadium catalyst systems (SIL1–3A(B)/V) for ethylene polymerization were obtained by immobilization of the Cp2VCl2 precursor (V) in the ionic liquid 1‐[3‐(triethoxysilyl)propyl]pyridinium chloride (IL), modified by AlCl3 and AlEtCl2 (A) or AlEt2Cl (B), and supported on three types of silica carrier S1–3. The properties of the ionic liquid supports were determined using Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller measurements, scanning electron microscopy and elemental analysis. The best re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The E-NB copolymers were prepared according to the procedures previously published [ 21 , 26 , 44 , 45 , 46 ]. The vanadium complexes with the following ligands were applied for the copolymerization reaction: 2-(4,5-dihydro-1,3-oxazolin-2-yl)phenol ( C1 ), 2-(4-methyl-4,5-dihydro-1,3-oxazolin-2-yl)phenol ( C2 ), 2-(5,6-dihydro-4H-1,3-oxazin-2-yl)phenol ( C3 ), 2-(1,3-oxazolin-2-yl)pyridine ( C4 ), 2,6-bis(1,3-oxazolin-2-yl)pyridine ( C5 ) and cyclopentadienyl ( C6 ) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E-NB copolymers were prepared according to the procedures previously published [ 21 , 26 , 44 , 45 , 46 ]. The vanadium complexes with the following ligands were applied for the copolymerization reaction: 2-(4,5-dihydro-1,3-oxazolin-2-yl)phenol ( C1 ), 2-(4-methyl-4,5-dihydro-1,3-oxazolin-2-yl)phenol ( C2 ), 2-(5,6-dihydro-4H-1,3-oxazin-2-yl)phenol ( C3 ), 2-(1,3-oxazolin-2-yl)pyridine ( C4 ), 2,6-bis(1,3-oxazolin-2-yl)pyridine ( C5 ) and cyclopentadienyl ( C6 ) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The SIL systems combine the advantages of homogeneous and heterogeneous catalysis, while reducing their disadvantages [ 42 , 43 ]. Moreover, our group showed that the SIL systems were active both in ethylene polymerization and copolymerization of ethylene with α-olefins and cyclic olefins [ 21 , 44 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study [33], the silica material with the narrow, but deep pores was chosen. The Brunauer-Emmett-Teller (BET) analysis shows that for this silica support, introduction of the ionic liquid and further modification by creation of more bulky chloroaluminate anion result in decrease of the surface area from 457 to 67 m 2 /g, like also in decreases of the pore volume from 0.56 cm 3 /g to 0.28 cm SEM images (Fig.…”
Section: Characterization Of Sil Vanadium Catalystmentioning
confidence: 99%
“…Vanadium salen complex, N,N 0 -ethylenebis(5-chlorosalicylideneiminato)vanadium(IV) dichloride-VCl 2 (salenCl 2 ), was obtained and prepared according to the published procedure [28]. Ionic liquid, 1-[3-(triethoxysilyl)propyl]pyridinium chloride, was obtained according to the published procedure [33].…”
Section: Experiments Materialsmentioning
confidence: 99%
See 1 more Smart Citation